No Acute Effects of Cannabidiol on the Sleep-Wake Cycle of Healthy Subjects: A Randomized, Double-Blind, Placebo-Controlled, Crossover Study - Linares, Ila M. P.; Guimaraes, Francisco S.; Eckeli, Alan; Crippa, Ana C. S.; Zuardi, Antonio W.; Souza, Jose D. S.; Hallak, Jaime E.; Crippa, José A. S. (Frontiers in Pharmacology, 2018)
Cannabidiol (CBD) is a component of Cannabis sativa that has a broad spectrum of potential therapeutic effects in neuropsychiatric and other disorders. However, few studies have investigated the possible interference of CBD on the sleep-wake cycle. The aim of the present study was to evaluate the effect of a clinically anxiolytic dose of CBD on the sleep-wake cycle of healthy subjects in a crossover, double-blind design. Twenty-seven healthy volunteers that fulfilled the eligibility criteria were selected and allocated to receive either CBD (300 mg) or placebo in the first night in a double-blind randomized design (one volunteer withdrew from the study). In the second night, the same procedure was performed using the substance that had not been administered in the previous occasion. CBD or placebo were administered 30 min before the start of polysomnography recordings that lasted 8 h. Cognitive and subjective measures were performed immediately after polysomnography to assess possible residual effects of CBD. The drug did not induce any significant effect (p > 0.05). Different from anxiolytic and antidepressant drugs such as benzodiazepines and selective serotonin reuptake inhibitors, acute administration of an anxiolytic dose of CBD does not seem to interfere with the sleep cycle of healthy volunteers. The present findings support the proposal that CBD do not alter normal sleep architecture. Future studies should address the effects of CBD on the sleep-wake cycle of patient populations as well as in clinical trials with larger samples and chronic use of different doses of CBD. Such studies are desirable and opportune.